If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 4y + -2x = 5 Reorder the terms: 5x + -2x + 4y = 5 Combine like terms: 5x + -2x = 3x 3x + 4y = 5 Solving 3x + 4y = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 3x + 4y + -4y = 5 + -4y Combine like terms: 4y + -4y = 0 3x + 0 = 5 + -4y 3x = 5 + -4y Divide each side by '3'. x = 1.666666667 + -1.333333333y Simplifying x = 1.666666667 + -1.333333333y
| (13-14)(2-4)= | | 6-b=17 | | 0.4y+8=1 | | (x^2+4)+(x^2+4)=16 | | (-3x-2)+4(1-x)=9(2x-5)-3(3x-5) | | (x^2+2)+(x^2+2)=16 | | 2(4y+36)=10(4y-204) | | 15+22(4+11)=x | | 8x-9=95 | | 10x-10-4=3x-27x+2 | | 8(-1+m)+3=2(m-5.25) | | y=-0.50(50)+128 | | 2+2(4-1)= | | 15x-8y=60 | | k+13*3=57 | | f(8)=-4x+1 | | k+13*3=57 | | 5x+(2-4x)=7 | | y=-0.50(40)+128 | | y=-0.50(40)+128 | | f(8)=-4x+1 | | x^3+18=143 | | x^3+18=143 | | x^3+18=143 | | x^3+18=143 | | x^3+18=143 | | x^3+18=143 | | x^3+18=143 | | x^3+18=143 | | 7x-19=72 | | 7x-19=72 | | x^3+18=143 |